THE EFFECT OF SERVICE QUALITY ON THE LEVEL OF SATISFACTION FORMAKING LAND CERTIFICATE IN BONDOWOSO REGENCY - Eka Zerli Defintasari; Muhammad Firdaus; Hary Sulaksono (STIE Mandala Jember, 2021)
This study aims to determine the quality of service to the satisfaction of the community in making the Land Certificate in the Land Office of Bondowoso district. This research was conducted at the Land Office, Bondowoso Regency. The population in this study is the Bondowoso community. The sampling method uses simple random sampling with questionnaire distribution techniques. The number of samples in this study were 55 respondents, namely applicants who came directly to the Land Office of Bondowoso Regency. The data analysis method in this study uses the Importance Performance Analysis (IPA) analysis and the Customer Satisfaction Index. Based on the results of data analysis, the variable with the largest gap in the Empathy Dimension is the gap value of -0.38 and the estimated gap is -0.1 in the Guarantee Dimension. This result also shows that the indicators of quality of certificate-making services whose level of importance is in accordance with the community are above average but are better than expected. Keywords:Service Quality, Public Satisfaction, Land Certificate